2010 7th IEEE Consumer Communications and Networking Conference 2010
DOI: 10.1109/ccnc.2010.5421735
|View full text |Cite
|
Sign up to set email alerts
|

Packet Loss Characteristics of IPTV-Like Traffic on Residential Links

Abstract: Abstract-Packet loss is one of the principal threats to quality of experience for IPTV systems. However, the packet loss characteristics of the residential access networks which carry IPTV are not widely understood. We present packet level measurements of streaming IPTV-like traffic over four residential access links, and describe the extent and nature of packet loss we encountered. We discuss the likely impact of these losses for IPTV traffic, and outline steps which can ameliorate this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Ellis et al [8] carried out experiments to characterize IPTV-lite traffic on residential links. The findings grouped packet loss in congestive and non-congestive losses, it was observed that congestive losses are the major cause of quality degradation and normally occur in bursts after queue overflow.…”
Section: Related Workmentioning
confidence: 99%
“…Ellis et al [8] carried out experiments to characterize IPTV-lite traffic on residential links. The findings grouped packet loss in congestive and non-congestive losses, it was observed that congestive losses are the major cause of quality degradation and normally occur in bursts after queue overflow.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, frequent update of encryption keys is desired to avoid unauthorized data sharing due to illegal key extracting. Although the data encryption is a well-designed technique 2 International Journal of Digital Multimedia Broadcasting in protecting sensitive data, its efficacy in IPTV environment can be affected based on the IP delivery characteristics such as packet loss [5,6]. In order to protect the multimedia stream against transmission errors/losses, forward error correction (FEC) deliberately produces redundant data to enable the reconstruction of any multimedia packets which are lost during transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Hohlfeld et al [34] provide a model to simulate packet loss packets based on Markov chains whose parameters are computed from session capture logs. Ellis and Perkins [14] characterize the packet losses in residential access networks (cable and ADSL), performing an intensive study of packet loss rates in 4 cable and 1 ADSL links, at several bitrates (1-4 Mbps). Most sequences had an error rate lower than < 1%.…”
Section: Other Topics Related To Qoe In Iptv Servicesmentioning
confidence: 99%